Differences in body composition between young soccer players (U19) members of the best soccer clubs in Serbia, Bosnia and Herzegovina, and North Macedonia - Gardasevic, J.; Bjelica, D.; Vasiljevic, I.; Masanovic, B. (Pedagogy of Physical Culture and Sports, 2020)
Background and Study Aim: The aim of this research was to determine the differences between the young soccer players (U19) in terms of anthropometric characteristics and body composition. We considered players of three the most successful clubs in three countries of the southern region of the Balkan Peninsula. Material and Methods: The first sub-sample of the subjects was consisted of 19 players of FC Radnicki from Serbia of the average age 17.84±.37. The second sub-sample was consisted of 19 players of FC Sarajevo from Bosnia and Herzegovina of the average age of 17.53±.51. The last sub-sample of the examinees was consisted of 13 players of FC Shkupi from North Macedonia of the average age 18.00±.00. Anthropometric characteristics in the body composition were evaluated by a battery of 11 variables. The significance of the differences between the young soccer players in the anthropometric characteristics and variables for assessing body composition were determined by ANOVA and LSD Post Hoc test. Results: The young soccer players of the three mentioned clubs have statistically significant differences by the two variables that estimate fat percentage and muscle mass. The young soccer players of FC Radnicki are significantly better in variable fat percentage than other players. The young soccer players of FC Skhupi have significantly less muscle mass than other players. Conclusions: The results can be useful for coaches of other clubs for making a comparison of their soccer players with the young soccer players in this research.